Optimisation of KUB-2 Chicken Growth to Increase Feed Efficiency Through Feed Restriction - Sabrina, Sabrina; Arlina, Firda; Subekti, Kusnadidi; Hellyward, James; Firdaus, Stevanny; Wulandari, Meri; Wulandari, Cici (AGRITROPICA : Journal of Agricultural Sciences, 2025)
This study aims to optimise the growth of Superior Balitbangtan (KUB-2) chickens through feed restriction during the starter period and its effect on the recovery phase. This study used 100 two-week-old KUB-2 chickens, placed in 20 cages measuring 70 cm x 70 cm x 60 cm, with each cage containing 5 KUB-2 chickens. The study employed a Completely Randomised Design (CRD) with four treatments and five replicates. The variables observed were feed intake, body weight gain, feed conversion ratio (FCR), Growth Rate,  and Income Over Feed Cost (IOFC). The research showed that applying 20%, 30%, and 40% feed restriction had a significant effect (P < 0.01) on decreasing feed intake and body weight gain, but had no significant effect (P > 0.05) on the feed conversion ratio during the 4 weeks of treatment. During the recovery phase, ad libitum feeding had a significant effect (P < 0.05) on feed intake, but did not affect body weight gain or feed conversion ratio. Throughout the study, feed restriction followed by recovery had a very significant effect (P < 0.01) on feed intake and a significant effect (P < 0.05) on body weight gain and feed conversion ratio. This study concludes that the 20% feed restriction treatment showed the best performance, with a feed intake of 339.97 g/bird/week, body weight gain of 98.35 g/bird/week, a feed conversion ratio of 3.46, a growth rate of 0.227, and an Income Over Feed Cost (IOFC) of Rp. 14,815.